Մարդու իրավունքների միջազգային-իրավական պաշտպանության հիմնախնդիրները Արցախի Հանրապետությունում - Գրիգորյան, Մարիամ
Факт, что лица входящие в состав населения Арцахской Республики с первого момента борьбы за самоопределения и правозглашения собственного государства и его международно-правового признания фактически лишены возможности защищаться нормами международного публичного права. В статье рассматриваются и обсуждаются проблемы и пути их решения, связанные с международной правовой защитой прав и законных интересов человека в Республике Арцах. It is a fact that humans who are part of the Artsakh Republic population are essentially deprived of the possibility of defending international public law from the beginning of the struggle for self-determination until the end of the proclamation of their own state and its international legal recognition. This article deals with the issues related to the international legal protection of the human rights and legal interests in the Artsakh Republic and the ways of their solution.
Keywords: Միջազգային իրավունք